PRESERVING HUMAN VALUES WITHIN MINANGKABAU CHILDREN ORAL STORIES THROUGH CREATIVE INDUSTRY (MELESTARIKAN NILAI-NILAI KEMANUSIAAN DALAM CERITA LISAN ANAK MINANGKABAU MELALUI INDUSTRI KREATIF) - Toti Sri Mulyati; Satya Gayatri; Yuhandri Yuhandri (Universitas PGRI Sumatera Barat, 2020)
Minangkabau is a territory situated in West Sumatra Indonesia. The history of Minangkabau comes from an oral tradition which is then written and known as